Producing Enhanced Yield and Nutritional Pigmentation in Lollo Rosso Through Manipulating the Irradiance, Duration, and Periodicity of LEDs in the Visible Region of Light - Cammarisano, Laura; Donnison, Iain S.; Robson, Paul R. H. (Frontiers in Plant Science, 2020)
Pigmented food are an important part of the human diet, and anthocyanins have demonstrable protection against tumor production in mouse models and beneficial effects on human liver chemistry. As such, producing pigmented crops is important for a nutritionally diverse diet. Lollo rosso lettuce is a fast-growing pigmented plant, is rich in phenolic compounds, and represents a suitable system to test optimization strategies for yield and anthocyanin production. High-energy UV wavebands are often used to stimulate increased pigmentation; however, we hypothesized that optimizing visible wavebands would deliver both yield and quality improvements. Growing Lollo rosso under irradiances between 5 and 180 W m–2 using visible waveband LEDs produced 0.4 g fresh weight per W m–2 in the linear portion of the curve between 5 and 40 W m–2 and achieved an approximate asymptote of 20 g fresh weight at around 100–120 W m–2 for yield. Anthocyanin content increased linearly with irradiance. We attempted to optimize the visible wavebands by supplementing half the asymptotic energy for 15 days with supplemental red (R) or blue (B) wavebands in the peaks of photosynthetic activity (430–460 and 630–660 nm). R and B affected rosette morphology with no significant impact on yield, but B significantly increased anthocyanin content by 94% compared to R. We therefore focused on further optimizing B by shortening the daily duration of supplemental B. The minimum B treatment that lacked significant pigment induction was 1 h. We hypothesized that short durations would be more active at different times in the diurnal cycle. Supplemental B was applied for 2 h at four different times. A night-break with B produced the highest yield and anthocyanin content. Our research demonstrates new ways to efficiently use readily available LEDs within the PAR wavebands to increase both yield and crop quality in controlled environment agriculture.